VOSviewer analysis of studies on software selection in the logistics sector - Doganer Duman, Bukra (Logistics, supply chain, sustainability and global challenges, 2024)
Outsourcing in logistics is an important step to reduce costs and increase operational efficiency. In this sense, it is possible to come across outsourcing in many areas of logistics processes. One of the outsourcing steps is the decision to select the software. Choosing the right software can affect the market share of the organization and the implementation time, effort, and cost. The findings of this research will help the marketing and sales teams of software product companies to develop key points and also enable end users to make informed decisions in selecting software packages for the organization. In this study, the studies in the literature were examined through the Scopus database, and co-citation analysis was performed using the VOSviewer program. As a result of the analysis, the articles analyzed were divided into four clusters and explained.
Keywords: izbor programske opreme; logistics; logistika; software selection; VOSviewer